Women's satisfaction with the childbirth experience: a descriptive research - Lara Menhart; Mirko Prosen (Nurses and Midwives Association of Slovenia, 2017)
Introduction: Satisfaction is a complex concept, which we often come across when evaluating the childbirth experience. The purpose of the research was to find out the childbirth experiences of women in Slovenia with regard to their level of satisfaction with the provided perinatal care. Methods: The Slovenian version of the Birth Satisfaction Scale - Revised was used in a non-experimental quantitative descriptive research (Cronbach α = 0.81). The data were collected through an online questionnaire in February 2017. Convenience sampling was used and 301 women, who gave birth in 2016 in Slovenia, participated. Data were analysed with descriptive statistics, the Mann-Whitney U test and Spearman's correlation coefficient. Results: The results of the study have shown that the number of births (U = 6802, p = 0.150), education (U = 7493, p = 0.317), age (U = 5142, p = 0.061) and presence of birth partner (U = 2841, p = 0.730) are not statistically significantly correlated with the assessment of childbirth satisfaction. A lower level of satisfaction was also found in cases of caesarean sections of primiparous, in comparison with multiparous, women (U = 430, p = 0.001). A statistically significant difference was established in the correlation between satisfaction and respondents' residential environment (U = 7029, p = 0.039), professional communication, and level of anxiousness of birthing mothers (rs = 0.397, p = 0,000). Discussion and conclusion: The results have shown that healthcare professionals who are present in childbirth are the key factor in contributing to a positive birth experience. The obtained results open up an opportunity for further research on the communication and attitude of health professionals towards birthing mothers.